Edukasi peningkatan kualitas pemulihan dan perawatan pasca operasi katarak - Kalbuadi, Heru; Rohmah, Anis Ika Nur (JOURNAL of Public Health Concerns, 2025)
Background: Cataract is the leading cause of global blindness, with a high prevalence in developing countries, including Indonesia. Cataract management through surgery requires adequate postoperative educational support, as patient and family knowledge plays a vital role in successful recovery. Health Education Communication (HEC) regarding eye wound care prior to patient discharge is considered crucial to prevent complications and accelerate healing. Purpose: Optimizing family knowledge and attitudes in supporting post-cataract surgery patient care to improve the quality of recovery and success of therapy. Method: The activity was conducted from July 28 to August 1, 2025, at Abdul Malik Fadjar Hospital, Sumbawa Regency, involving eight families of postoperative cataract patients selected purposively. The educational intervention consisted of a 3-minute video screening and a 10–15-minute direct counseling session, followed by assessment of knowledge and practice using pre-test and post-test questionnaires. Evaluation was carried out using 10 items in multiple-choice and yes/no formats, scored from 0 to 10, with qualitative interpretation of knowledge categories: Good (76–100%), Fair (56–75%), and Poor (<56%). Results: The majority of respondents were aged 31–40 years (50%), female (75%), held a higher education degree (50%), worked as entrepreneurs (50%), and were the children of postoperative cataract patients (62.5%). Pre-test evaluation showed that 50% of respondents had fair knowledge, while post-educational intervention results indicated a significant improvement, with 75% of respondents achieving a good knowledge category. Conclusion: Health education has proven effective in enhancing the knowledge of families of postoperative cataract patients, particularly among productive age groups, women, and those with higher education. The provided education successfully improved understanding and reinforced confidence in caregiving, thereby significantly supporting postoperative recovery outcomes. Suggestion: The postoperative cataract care education program is recommended to be implemented continuously across various healthcare facilities with broad coverage, including communities with low educational backgrounds and inflexible occupations. Educational materials should be tailored to the demographic characteristics of participants to ensure information is easily understood and capable of enhancing motivation and accuracy in caregiving practices by patients’ families. Keywords: Care; Cataract; Education; Postoperative Pendahuluan: Katarak merupakan penyebab utama kebutaan global, dengan prevalensi tinggi di negara berkembang termasuk Indonesia. Penatalaksanaan katarak melalui pembedahan memerlukan dukungan edukasi pascaoperasi yang memadai, karena pengetahuan pasien dan keluarga berperan penting dalam keberhasilan pemulihan. Komunikasi Informasi Edukasi (KIE) tentang perawatan luka mata sebelum pasien pulang dinilai krusial untuk mencegah komplikasi dan mempercepat penyembuhan. Tujuan:  Mengoptimalkan pengetahuan dan sikap keluarga dalam mendukung perawatan pasien pascaoperasi katarak guna meningkatkan kualitas pemulihan dan keberhasilan terapi. Metode: Kegiatan dilaksanakan pada 28 Juli–1 Agustus 2025 di Rumah Sakit Abdul Malik Fadjar, Kabupaten Sumbawa, dengan melibatkan 8 keluarga pasien pascaoperasi katarak yang dipilih secara purposive. Intervensi edukasi dilakukan melalui pemutaran video berdurasi 3 menit dan penyuluhan langsung selama 10–15 menit, diikuti pengukuran pengetahuan dan praktik menggunakan kuesioner pre-test dan post-test. Evaluasi dilakukan dengan 10 item soal pilihan ganda dan pilihan ya/tidak, dengan skor 0–10 dan interpretasi kategori pengetahuan secara kualitatif: Baik (76–100%), Cukup (56–75%), dan Kurang (<56%). Hasil: Mayoritas responden berusia 31–40 tahun (50%), perempuan (75%), berpendidikan perguruan tinggi (50%), bekerja sebagai wiraswasta (50%), dan merupakan anak dari pasien pascaoperasi katarak (62,5%). Evaluasi pre-test menunjukkan 50% responden memiliki pengetahuan cukup, sementara setelah intervensi edukasi, terjadi peningkatan signifikan dengan 75% responden mencapai kategori pengetahuan baik. Simpulan: Penyuluhan kesehatan terbukti efektif meningkatkan pengetahuan keluarga pasien pascaoperasi katarak, khususnya pada kelompok usia produktif, perempuan, dan berpendidikan tinggi. Edukasi yang diberikan mampu memperbaiki pemahaman dan memperkuat keyakinan dalam perawatan, sehingga mendukung keberhasilan pemulihan pascaoperasi secara signifikan. Saran: Program edukasi perawatan pascaoperasi katarak disarankan dilaksanakan secara berkelanjutan di berbagai fasilitas kesehatan dengan cakupan luas, termasuk masyarakat berpendidikan rendah dan berpekerjaan tidak fleksibel. Materi penyuluhan perlu disesuaikan dengan karakteristik demografis peserta agar informasi mudah dipahami dan mampu meningkatkan motivasi serta ketepatan praktik perawatan oleh keluarga pasien.